2019
DOI: 10.1021/acs.analchem.9b02038
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Specific Sulfur Isotope Analysis by Liquid Chromatography Coupled to Multicollector ICPMS

Abstract: An accurate method has been developed to measure, in a single analytical run, δ 34 S in sulfite, sulfate and thio-sulfate in water samples by liquid chromatography combined with multicollector inductively coupled plasma mass spec-trometry (MC-ICPMS). The method is based on the anionic exchange separation of sulfur species prior to their online isotope ratio determination by MC-ICPMS. Mass bias correction was accomplished by a novel approach based on the addition of an internal sulfur-containing standard to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…During the last 15 years, multiple-collector inductively coupled plasma mass spectrometry (MC-ICPMS) has been developed and mainly used for sulfur isotope analysis of inorganic compounds. Although MC-ICPMS does not allow precise δ 36 S analysis due to interference by 36 Ar + , analytical precisions similar to IRMS methods have been achieved for δ 33 S and δ 34 S in bulk inorganic material in samples containing only a few nanomoles. Another study demonstrated that precise (σ < 0.3 mUr) δ 34 S analysis in individual S-containing anions is feasible by coupling ion chromatography with MC-ICPMS. , This method is based on the online separation of anionic species prior to their isotope analysis by MC-ICPMS. Thus, it significantly simplified the sample preparation and additionally allowed for the analysis of several sulfur-containing species as transient signals in a single run.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 15 years, multiple-collector inductively coupled plasma mass spectrometry (MC-ICPMS) has been developed and mainly used for sulfur isotope analysis of inorganic compounds. Although MC-ICPMS does not allow precise δ 36 S analysis due to interference by 36 Ar + , analytical precisions similar to IRMS methods have been achieved for δ 33 S and δ 34 S in bulk inorganic material in samples containing only a few nanomoles. Another study demonstrated that precise (σ < 0.3 mUr) δ 34 S analysis in individual S-containing anions is feasible by coupling ion chromatography with MC-ICPMS. , This method is based on the online separation of anionic species prior to their isotope analysis by MC-ICPMS. Thus, it significantly simplified the sample preparation and additionally allowed for the analysis of several sulfur-containing species as transient signals in a single run.…”
Section: Introductionmentioning
confidence: 99%
“…19−23 Another study demonstrated that precise (σ < 0.3 mUr) δ 34 S analysis in individual S-containing anions is feasible by coupling ion chromatography with MC-ICPMS. 24,25 This method is based on the online separation of anionic species prior to their isotope analysis by MC-ICPMS. Thus, it significantly simplified the sample preparation and additionally allowed for the analysis of several sulfur-containing species as transient signals in a single run.…”
Section: ■ Introductionmentioning
confidence: 99%
“…89 Interest in Hg is also growing because of the mass-dependent and mass-independent fractionation effects observed in the environment. 90 Other elements of interest include Nd 91 for geochemical dating purposes, B 92,93 for paleoclimate reconstruction, S 94 for source investigations, and Fe, Zn, Cu and Ca in human samples. 95 This last application field studies isotopic fractionation in humans as diagnostic tools in the detection of diseases.…”
Section: Applications Of Isotopic Measurementsmentioning
confidence: 99%
“…The hyphenated systems introduce the possibility to analyse several species within one run, drastically decrease analysis time, increase sample throughput, and minimize "human error". 3,10 However, the main limitation of on-line isotope analysis with hyphenated systems is the decrease of the precision due to generation of short transient signals. 11 There are several reasons that cause the decrease in precision: (i) transient signals occur in a certain time window of several seconds, thus the total measurement time as well as the commonly applied integration time are considerably lower compared to a continuous sample introduction of several minutes, (ii) the transient signals comprise peak shapes with substantial variations in intensity, thus the weights of points are not equal, (iii) depending on the separation technique, the injected amount of sample might be signicantly lower than the amount of sample processed with off-line separation, thus the signal intensity of the respective isotopes are generally low with hyphenated systems.…”
Section: Introductionmentioning
confidence: 99%